Fine-scale spatial associations between functional traits and tree growth - Fajardo, Alex; Velazquez, Eduardo (My University, 2021)
The effective use of functional traits to explain species coexistence has been hindered by the scarce use of demographic variables, such as growth, with the association between functional traits and growth often assumed rather than tested. In this study, using spatial point-pattern analyses, we spatially related three functional traits linked to plant competitive ability (maximum tree height [H-MAX], leaf mass per area [LMA] and wood density [WD]) to tree growth rates (basal area increment [BAI(10)] and growth efficiency [GE]) in a stem-mapped plot of a temperate rainforest in southern Chile. With this, we tested the competition-trait similarity and the competition-trait hierarchy hypotheses, and further assessed the relationship between functional trait values' spatial distribution and growth rate. We used spatial point-pattern analyses, in particular, pair-wise spatial association patterns, the Schlather's I index and mark variograms associated to specific null models to infer spatial correlations among individuals of several species with different traits and growth values. First, we found spatial similarity in trees' functional traits on a fine-scale, a result supporting the competition-trait hierarchy hypothesis. Second, while the H-MAX and LMA specific values of the focal tree were spatially positively correlated with their neighbours' growth rates, the WD of the focal tree had a negative spatial correlation with its neighbours' growth rates. We also found a positive spatial autocorrelation among H-MAX, LMA and WD at a fine-scale; neighbouring trees tended to have similar values. In agreement with our a priori statements, we infer that H-MAX and LMA provide a competitive tolerance, while WD of the focal tree has a competitive effect on its immediate neighbours. As such, we have demonstrated that functional traits mediate species interactions, which is a step forward in predictive community ecology, thus we can further our understanding regarding how traits mediate community assembly and species coexistence.
Keywords: community ecology; patagonia; plant-plant interactions; temperate rainforest; wood density